Perancangan Sistem Informasi Manajemen Pelayanan Bank Darah Pada Rumah Sakit Umum Harapan Ibu Purbalingga - MARKOYO, MARKOYO (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Bina Sarana Informatika, 2023)
Abstract - The Blood Bank Unit at RSU Harapan Ibu Purbalingga or commonly referred to as the BDRS Unit, is a medical support unit located at RSU Harapan Ibu Purbalingga, having its address at JL. Major General Soengkono KM 1 Purbalingga in charge of providing blood for hospital needs only. In providing blood stock, the Hospital BDRS Unit has collaborated with PMI Purbalingga and PMI Banyumas, so it is hoped that the need for blood stock in hospitals can always be met. As for blood supply activities for hospital patients, every patient who will need blood, health workers or nurses will make a request for blood to the BDRS Unit. In carrying out its activities, the BDRS Unit is required to be able to serve quickly, effectively and efficiently. However, there are some obstacles because the system is still manual, such as recording incoming blood, outgoing blood, blood stock information and searching patient history. Therefore, an Information System is needed that can assist BDRS officers in carrying out their duties. This information system is made using the Waterfall Method. Made with the Code Ignitier Framework, using the PHP programming language, Javascript, Html. While the database uses MySQL. From the results of the study, it was concluded that this system could assist officers in the BDRS Unit in managing incoming and outgoing blood transactions and providing information on blood stock, patient history and required reports. This system also helps nurses see real-time blood stock information in the BDRS Unit. Keywords: Information System Design, Blood Bank, Hospital